Ocular manifestations of childhood acute leukemia in a tertiiary level eye centre of Kathmandu, Nepal - Khadka, Deepak; Sharma, Ananda; Shrestha, Jeevan K; Shrestha, Gauri S; Shrestha, Pun N; Pant, Suresh R; Pant, Bidya P (Nepalese Journal of Ophthalmology, 2014)
Introduction: In some instances, the understanding of the ocular manifestations in childhood leukemia is not only important to establish the diagnosis but also reflects the disease state and prognosis. Objective: To study the ocular manifestations of childhood acute leukemia among the children attending a tertiary-level hospital in Nepal. Materials and methods: A cross-sectional, descriptive study was undertaken at the B.P. Koirala Lions Centre for Ophthalmic Studies (BPKLCOS) and Kanti Children Hospital (KCH), Kathmandu, over a period of one-and-a-half years. Children diagnosed with acute childhood leukemia referred to the BPKLCOS from the Oncology Unit of the KCH and the Emergency Department of the Tribhuvan University Teaching Hospital (TUTH) were included in the study, using a non-probability sampling method. Results:Of the 71 cases with childhood acute leukemia, 55 (77.5%; 95% CI = 66% - 85%) had acute lymphoblastic leukemia(ALL)whereas the other 16 (23%) had acute myeloblastic leukemia (AML). Ocular involvement were seen in 33 cases (46%) and were more frequent in cases of AML as compared to those with ALL (p=0.001, OR 5.0, 95% CI= 1.4 – 17.5). Direct ocular involvement and secondary ocular involvement were observed in 12 (16.9%) and 29 (40.8%) subjects, respectively. Ocular symptoms were present in only 11 cases (15.49%). Cerebro-spinal fluid (CSF) and bone marrow examination in cases with direct ocular involvement showed 10 cases (83.3%) positive for blast cells in the CSF and 6 cases (50%) positive for blast cells in bone marrow. The most common secondary manifestation was retinal haemorrhage, seen in 23 cases (32.4%). Conclusion: In view of the high asymptomatic ocular involvement and the significant visual morbidity, a routine ophthalmic examination is recommended as an integral part of the medical examination in all cases of childhood acute leukemia. DOI: http://dx.doi.org/10.3126/nepjoph.v6i2.11678 Nepal J Ophthalmol 2014; 6(12): pp. 197-204